Tailoring Ti3C2Tx MXene Flake Sizes for Modified Electrochemical Performance: A Top-down Approach - Fan, Yuchao; Mei, Xu; Ye, Li; Tian, Qingyong; Zhang, Renqi; Zhang, Yingjiu; Li, Xinjian (Current Physics, 2024)
IntroductionTwo-dimensional (2D) materials, such as MXene (Ti3C2Tx), have garnered extensive attention in recent years due to their exceptional performance across various domains. The flake size of Ti3C2Tx notably influences its specific surface area, a pivotal factor in interfacial interactions within electrochemistry.MethodsPresently, modifying the flake size of bulk Ti3C2Tx typically involves complex and costly processes, like ultrasonic treatment and isolation. Leveraging the specific preparation principle of MXenes, which involves etching the A layers in precursor MAX phases, a top-down strategy for producing Ti3C2Tx flakes of desired sizes, has been proposed in this work. In this approach, precursor Ti3AlC2 particles undergo ball-milling to adjust their size.ResultsThrough this innovative strategy, dispersions of Ti3C2Tx flakes with varying average lateral sizes are generated, enabling an investigation into the impact of lateral size on the electrochemical properties of Ti3C2Tx flakes. By controlling the ball milling time for Ti3AlC2 powders, the resulting average sizes of Ti3C2Tx (0, 2, 4) are 6.34 μm, 2.16 μm, and 0.96 μm, respectively. Particularly, the Ti3C2Tx (2) electrode, composed of 2.16 μm sheets, demonstrates remarkable performance metrics. It exhibits a high areal capacitance of 845.0 mF/cm2 at a scan rate of 5 mV/s, along with a gravimetric capacitance of 244.0 F/g at a current density of 1 A/g.ConclusionThis study presents a facile method to enable mass production of Ti3C2Tx with sheets of varying sizes, addressing both small and large dimensions.
Keywords: Mxene